Joining forces in Ochnaceae phylogenomics: a tale of two targeted sequencing probe kits. Issue 7 (27th June 2021) - Shah, Toral; Schneider, Julio V.; Zizka, Georg; Maurin, Olivier; Baker, William; Forest, Félix; Brewer, Grace E.; Savolainen, Vincent; Darbyshire, Iain; Larridon, Isabel
Abstract : Premise: Both universal and family‐specific targeted sequencing probe kits are becoming widely used for reconstruction of phylogenetic relationships in angiosperms. Within the pantropical Ochnaceae, we show that with careful data filtering, universal kits are equally as capable in resolving intergeneric relationships as custom probe kits. Furthermore, we show the strength in combining data from both kits to mitigate bias and provide a more robust result to resolve evolutionary relationships. Methods: We sampled 23 Ochnaceae genera and used targeted sequencing with two probe kits, the universal Angiosperms353 kit and a family‐specific kit. We used maximum likelihood inference with a concatenated matrix of loci and multispecies‐coalescence approaches to infer relationships in the family. We explored phylogenetic informativeness and the impact of missing data on resolution and tree support. Results: For the Angiosperms353 data set, the concatenation approach provided results more congruent with those of the Ochnaceae‐specific data set. Filtering missing data was most impactful on the Angiosperms353 data set, with a relaxed threshold being the optimum scenario. The Ochnaceae‐specific data set resolved consistent topologies using both inference methods, and no major improvements were obtained after data filtering. Merging of data obtained with the two kits resulted in a well‐supported phylogenetic tree. Conclusions: The Angiosperms353 data set improved upon data filtering, and missing data played an important role in phylogenetic reconstruction. The Angiosperms353 data set resolved the phylogenetic backbone of Ochnaceae as equally well as the family specific data set. All analyses indicated that both Sauvagesia L. and Campylospermum Tiegh. as currently circumscribed are polyphyletic and require revised delimitation.